P3.170 Women, harm reduction and hiv. (8th July 2017) - Mbugua, Njeri; Bukusi, Elizabeth Ann; Wagura, Asunta; Ngugi, Elizabeth
Abstract : Introduction: This paper compares and contrasts number of partners and condom use behaviour for female sex workers and a sample of women working in other economic activities, with both samples drawn from the large informal settlement of Kibera, Nairobi. Methods: As expected, univariate analysis revealed much higher numbers of overall sexual partners and higher levels of condom use among female sex workers compared to Kibera women in other occupations. An unexpected finding, however, was that female sex workers with a romantic partner had significantly fewer sexual partners per unit time than female sex workers without such a partner. Results: This finding held for multivariate analysis, with negative binomial regression analyses showing that having a romantic partner was significantly associated with reductions in total number of both sexual partners overall and with sexual partners who did not use condoms. In contrast, HIV status, education, number of immediate family members and levels of alcohol consumption were non-significant factors for both regression analyses. Conclusion: Results suggest that female sex workers' romantic partners act as more than sources of possible HIV infection; rather, romantic partners appear to have an important positive impact on health. We discuss this finding in light of possible harm-reduction programmes focusing on female sex workers and their romantic partners.